Maternal and fetal outcome of comparative study between old & adopted new value of screening of Gestational Diabetes Mellitus in tertiary centre in Saudi Arabia - Farid, Gehan; Kamal, Reem Mohammed; Swaraldahab, Mohamed AH; Ali, Sarah Rabie (Clinical Journal of Obstetrics and Gynecology, 2018)
Objectives: To check if there is any significant difference in the immediate outcome of pregnancy with diabetes using the new values of FBS & 2hrs post prandial with 75g OGTT for 1 year (from 1st June 2013-31st May 2014) in comparison to the previous data done in the same institute with other values and with international figures. The data in our study included fetal, maternal morbidities, intra partum and postnatal outcomes, in order to help, if possible, on deciding the best values to use for screening for gestational diabetes mellitus. Furthermore, to know the new percentages of gestational diabetes mellitus in SFH by utilizing the new values of Blood Sugar readings. Design: Retrospective cohort study Setting: Security Forces Hospital-Riyadh-Saudi Arabia Patients: Done (from 1st June 2013 – 31st May 2014), on patients who had attended Security Forces Hospital, Riyadh, Saudi Arabia. This chosen year’s data was compared with data collected in the three previous years using different figures. Main Outcome measured: Average age of mother, maternal aspects of parity, history of GDM, number of abortions``````````````````````````````, estimated blood loss in labor, associated medical disorder, complications of previous pregnancies, methods of control of GDM, gestational age for IOL and associated intrapartum complications. Immediate neonatal outcome in cases of GDM, comparison of birth weights of babies & any specific congenital abnormalities and delayed causes of admission to NICU in the 4 years studied were also reviewed. Results: The percentage of diagnosed cases of gestational diabetes mellitus (GDM) after screening was 24 % as compared with 14.5% in previous study of 2003-2004 & with the number of screened patients amounting to 93% out of the total number of deliveries between 2013-2014 (in both years universal method of screening was used). The multidisciplinary set up of our GDM specialized clinic which was composed of dieticians, diabetic educators, endocrinologists and obstetric physicians operating together, helped to reduced the use of insulin in combination with diet to only 24% in comparison to 76% of patient using diet and exercise alone. The study showed a mean age of 33years and weight of 77kg. It was also noted that 16% of the patients diagnosed with GDM were multiparous averaging 1-5 deliveries. Almost 62% of patient didn’t give any history of GDM and no history of previous medical diseases. The majority of the patient with GDM delivered without complications during labor, with 30% having vaginal lacerations & 73% of patient had an estimated blood loss of less than 500cc. NICU admissions secondary to hyperbilirubinaemia averaged almost 17% in comparison to previous studies and only one baby expired in a GDM patient. Our study revealed a good fetal and maternal out come with less delivery complications and less incidence of postpartum hemorrhage (5.7%). Conclusion: It is concluded that Universal Screening of Pregnant women whether with previously used glucose value or new ones for gestational diabetes mellitus is a better option, which has proven to improve both maternal and fetal outcomes. The 75 OGTT test is a cost effective test and with both easy accessibility and good screening pick up number (92.5%) of the patients in Security Forces Hospital, Riyadh. Recommendation: We recommend annual follow up for patients, both the mother and the baby after postpartum, to prevent the development of type 2 diabetes.